Data from the Indian drug regulator and from Clinical Trials Registry-India does not always match - Bhalla, Iqbal S.; Ravindranath, Adithi Gopadi; Vaswani, Ravi; Saberwal, Gayatri (Frontiers in Medicine, 2024)
Introduction In India, regulatory trials, which require the drug regulator’s permission, must be registered with the Clinical Trials Registry-India (CTRI) as of 19 March 2019. In this study, for about 300 trials, we aimed to identify the CTRI record that matched the trial for which the regulator had given permission. After identifying ‘true pairs’, our goal was to determine whether the sites and Principal Investigators mentioned in the permission letter were the same as those mentioned in the CTRI record. Methods We developed a methodology to compare the regulator’s permission letters with CTRI records. We manually validated 151 true pairs by comparing the titles, the drug interventions, and the indications. We then examined discrepancies in their trial sites and Principal Investigators. Results Our findings revealed substantial variations in the number and identity of sites and Principal Investigators between the permission letters and the CTRI records. Discussion These discrepancies raise concerns about the accuracy and transparency of regulatory trials in India. We recommend easier data extraction from regulatory documents, cross-referencing regulatory documents and CTRI records, making public the changes to approval letters, and enforcing oversight by Institutional Ethics Committees for site additions or deletions. These steps will increase transparency around regulatory trials running in India.